Possible Functions of the Course Books in Practice Focused Subjects and in the Learning Process (Training and Practice : Journal of Educational Sciences, 2010)
The traditional learning-centred teaching will be replaced by learner-centred practice, the normative didactics by empiric tendency. Areas of development: learner centred planning, teacher activity enhancing common thinking, development of creativity. I analysed the role and functions of the course books of „Hon- és népismeret” (National and folk studies). The course book is the main source of knowledge but it is losing its vital role. Points of the conception: academic knowledge, practice-centredness, interdisciplinar competence, multidimensional methodological competence. I present the concept, the functions of the course book with the help of static-, dynamic- and learning-centred approach. After the analysis of the course book I concluded that the sole use of the course books does not enhance learning activities, practice or creativity during the acquisition of the course material. The course books need to be renewed.